When we were very young - Milne, A. A. 1882-1956. (Alan Alexander); Shepard, Ernest H. 1879-1976, (Ernest Howard) (New York, N.Y., U.S.A. : Puffin Books, 1992)
A collection of poems reflecting the experiences of a little English boy growing up in the early part of the twentieth century.
Originally published: New York : E.P. Dutton, 1924.
Keywords: Children's poetry, English; English poetry